Centers and peripheries in the 21st Century: Bulgaria and the Middle East (Philology, 2023)
Guiding concepts in the social sciences are often presented in the abstract. Yet notions such as center and periphery are intimately tied to the historical contexts in which they are created. Thus, center and periphery in its original form was closely linked to the “modernization” theory that dominated the social sciences from the 1950s through the end of the 20th century. Recognizing such concepts in their historical settings facilitates understanding their initial appeal and limits. The author narrates his own involvement with social theory, Islamic studies, and the rapprochement of anthropology and history, and development of the concept of centers and peripheries, especially as it was shaped by an ongoing multi-year social historical and anthropological project anchored in Bulgaria.
Keywords: centers and peripheries; Islam; regions; Islamic studies; anthropology; social history